(untitled) (Journal of Contemporary Studies, 2022)
The book divides the history of American Foreign Policy into Four Ages for comprehensive understanding of readers, each defined by a consistent increase in the country’s power in its relations with others. Three unique features of American foreign policy are the ideological goals of foreign policy, the use of economic instruments in pursuing them, and a democratic process for formulating and implementing decisions about it.